2019
DOI: 10.2169/internalmedicine.2684-19
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Endophthalmitis Associated with Pyogenic Liver Abscess Caused by <i>Klebsiella pneumoniae</i>

Abstract: We report 2 cases of endogenous endophthalmitis associated with pyogenic liver abscess caused by Klebsiella pneumoniae. Case 1 involved a 70-year-old woman and case 2 involved a 50-year-old man who were admitted to our hospital with diagnoses of liver abscess and endogenous endophthalmitis, respectively. The liver abscess resolved with antibiotics and percutaneous transhepatic drainage in case 1 and with antibiotics alone in case 2. Even though both cases underwent ophthalmic surgery, they were discharged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…The entry gate is considered to be the gastrointestinal tract [ 15 ], oropharyngeal [ 67 ], or recent urinary tract infections [ 62 ]. Oropharyngeal colonization could lead to infection with aspiration, but it is still unclear what the mechanism of entry is via the GI tract since many individuals subsequently infected have no apparent GI pathology.…”
Section: Epidemiology Of Endogenous Hvkp Endophthalmitis (Eke)mentioning
confidence: 99%
See 2 more Smart Citations
“…The entry gate is considered to be the gastrointestinal tract [ 15 ], oropharyngeal [ 67 ], or recent urinary tract infections [ 62 ]. Oropharyngeal colonization could lead to infection with aspiration, but it is still unclear what the mechanism of entry is via the GI tract since many individuals subsequently infected have no apparent GI pathology.…”
Section: Epidemiology Of Endogenous Hvkp Endophthalmitis (Eke)mentioning
confidence: 99%
“…Chung et al found a significant fecal carriage of K1 and K2 pathogenic stains in stools in a cohort of healthy South Korean residents [ 15 ]. Fujita et al found a correlation with previous treatments with ampicillin or amoxicillin, leading to the hypothesis that these antibiotics may increase the risk for KPLA by selection pressure [ 67 , 68 , 69 ]. Diabetes, by impaired gastrointestinal permeability, may favor bacterial translocation into the portal bloodstream [ 68 , 69 ].…”
Section: Epidemiology Of Endogenous Hvkp Endophthalmitis (Eke)mentioning
confidence: 99%
See 1 more Smart Citation
“…KLA has an overall good prognosis if diagnosed early and treated adequately, but patients with metastatic infection especially endophthalmitis have a poor prognosis and cause significant morbidity [15].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous endophthalmitis as a result of liver abscess is caused by the hematogenous spread of pathogenic bacteria from the liver abscess, which passes through the blood–retinal barrier, leading to infection of the eye [ 3 ]. In recent years, many cases have been reported in Asia, with Klebsiella pneumoniae being the most common causative agent [ 4 , 5 ]. Since the disease is relatively occult during the early stage, it can rapidly infect intraocular tissues, resulting in irreversible damage to the photoreceptor cells in the retina.…”
Section: Introductionmentioning
confidence: 99%